Determination of Moment Capacity Mp for Rectangular Reinforced Concrete Columns - Aydemir, Cem; Zorbozan, Mustafa; Alacali, Sema Noyan (TURKISH CHAMBER CIVIL ENGINEERS, 2009)
Turkish Seismic Code obligates the capacity design procedure for the calculation of the design shear force of RC beams and columns. Therefore, the plastic hinge moment capacity (M-p) at the ends of the column must be determined as realistic as possible. Turkish Seismic Design Code recommends an increase of 40% in ultimate moment capacity (M-r) to obtain the plastic hinge moment capacity (M-p), unless a detailed calculation is carried out. However, this recommendation remains insufficient to obtain plastic hinge moment capacity for high levels of axial load. In this Study, new analytical equations have been derived to obtain the plastic hinge moment capacity of rectangular RC columns in a realistic and practical way. Plastic hinge moment capacity of columns calculated with proposed equations is compared to the capacity extracted from experimental results. It is shown that proposed equations yield realistic results.
Keywords: Column moment capacity; M-N interaction diagrams; strain hardening; confined concrete; Engineering